Thermomechanical enhancement of DPP‐4T through purposeful π‐conjugation disruption. Issue 3 (15th September 2021) - Callaway, Connor P.; Bombile, Joel H.; Mask, Walker; Ryno, Sean M.; Risko, Chad
Abstract: The design of polymer‐based organic semiconductors that offer mechanical deformability while maintaining efficient semiconducting characteristics remains a significant challenge. Recent synthetic efforts have incorporated small alkyl segments directly into otherwise π‐conjugated polymer backbones to enhance processability, mechanical deformability, and other properties. The resulting polymers can be used as stand‐alone materials or as matrix polymers in complementary semiconducting polymer blends offering reasonable charge‐carrier transport properties, thermal healing, and deformability. Here, a family of diketopyrrolopyrrole‐tetrathiophene variants is explored via large‐scale atomistic molecular dynamics simulations to examine the effect of alkyl segments incorporated into the polymer backbone on the polymer structure, dynamics, and thermal properties. Longer alkyl segments lead to polymer chains that are more flexible, compact, and mobile, with lower glass transition temperatures for the condensed phase. Abstract :